If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 6x + 1 = 5x Reorder the terms: 1 + 6x = 5x Solving 1 + 6x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 6x + -5x = 5x + -5x Combine like terms: 6x + -5x = 1x 1 + 1x = 5x + -5x Combine like terms: 5x + -5x = 0 1 + 1x = 0 Add '-1' to each side of the equation. 1 + -1 + 1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 0 + -1 1x = 0 + -1 Combine like terms: 0 + -1 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1

| 3x^3-4x^2-5x+2=0 | | 9a+15=10a-7 | | -t=14 | | 9x-3x+x=-4 | | 3g+5+2g+3= | | -3(k-4)=-6 | | 7x^2+12x-27=0 | | 9y+7=8y-6 | | 1+6=10x | | y+14x=37 | | 3(a-4)=9 | | 3x-2y+1=0 | | x^4+6x^2-27=0 | | 5+1=2 | | 9q-3p+7p= | | (2x-1)(x+2)=-3 | | 9m+4n-5n= | | (x+2)*(x+2)=-7 | | 2x*x=9 | | 2x*x=4 | | x^2-2.05x+1=0 | | 3x-2=-17 | | 8x+20=30-2x | | 16x^3-7=x-112x^2 | | 2x*c=45 | | 2x*x=45 | | 6x+2=17+3x | | 8x^2+5=805 | | (x+6)(x-9)=6 | | 13x-2=5x+22 | | 2x*x=2 | | 2x-3x=22 | | 34x+768y=23 | | 3x*3x+4=19 | | 8-(2-3a)=8(3-2a)-a | | 2.4524x+1.3766y=0.4637 | | 3(x+4)=3x-2 | | u-3=5 | | -3x+7=5x+1 | | 6+4=8a | | x^2+75=0 | | 15-6x-13-7x= | | x^2+75x=0 | | 6(9+x)=14(-6-x) | | 11m+2n-3m+4mn+5m-2= | | x-7=6x-6 | | 6x-8=2x-6 | | 6(3+x)=5(5-x) | | 2x+3=-2x+8 | | 16+5x=3x-6 | | 5x-21=8 | | 9x-1=13x+4 | | 16+5x=3x-76 | | 3d+14d+8= | | 2m^2-10-28= | | (2t+3)(t+4)= | | 2x^2+5x+990=0 | | -x^2+14x+75=0 | | -12x+49=18 | | x=15+0.3x | | 15=x-0.13x | | x=15+0.13x | | 6s+2s-3d-2d= | | -x^2+12x+36-2+x^2+10x+25-x^2-8x+16=0 | | 6a+b+3c+b+3a+3c= |